Detection of simple mutations and polymorphisms in large genomic regions - Sokurenko, Evgeni V. (Oxford University Press, 2001)
We have developed a novel technology that makes it possible to detect simple nucleotide polymorphisms directly within a sample of total genomic DNA. It allows, in a single Southern blot experiment, the determination of sequence identity of genomic regions with a combined length of hundreds of kilobases. This technology does not require PCR amplification of the target DNA regions, but exploits preparative size-fractionation of restriction-digested genomic DNA and a newly discovered property of the mismatch-specific endonuclease CEL I to cleave heteroduplex DNA with a very high specificity and sensitivity. We have used this technique to detect various simple mutations directly in the genomic DNA of isogenic pairs of recombinant Pseudomonas aeruginosa, Escherichia coli and Salmonella isolates. Also, by using a cosmid DNA library and genomic fractions as hybridization probes, we have compared total genomic DNA of two clinical P.aeruginosa clones isolated from the same patient, but exhibiting divergent phenotypes. The mutation scan correctly detected a GA insertion in the quorum-sensing regulator gene rhlR and, in addition, identified a novel intragenomic polymorphism in rrn operons, indicating very high stability of the bacterial genomes under natural non-mutator conditions.